POLITENESS PRINCIPLES IN BARRACK OBAMA’S INTERVIEW - Conny Elisabeth; Willem Saragih (LINGUISTICA, 2014)
ABSTRACT This study was focused on the types of politeness principles. This research was conducted by using descriptive qualitative design. The data were the transcript of Barrack Obama’s interviews which were downloaded from internet. The findings showed that there were 31 utterances which contained 6 types of politeness principles. Obama tended to use the expressions of agreement maxim (51,61%), approbation maxim (22,58%), generosity maxim (12,9%), tact maxim (6,45%), modesty maxim (3,22%), and sympathy maxim (3,22%). The most dominant type of politeness principles was agreement maxim which means that Obama tried to minimize disagreement between self and others and maximize agreement between self and others. Keyword :  politeness principles, types of politeness principles, interview.